1980
DOI: 10.2190/4kg5-hbh0-nnme-dm58
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Death Anxiety: A Review of Empirical Studies

Abstract: Correlational studies of the fear of death completed over the last decade are reviewed. Research topics, trends, and findings are compared to earlier research on death anxiety correlates. Emphasis is placed on definitions of the construct, measurement techniques, concepts of death, and the variables of sex, age, occupation, socioeconomic status, value orientation, levels of awareness, and relationships between death anxiety and an array of personality variables. Suggestions for future areas of research are mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
6

Year Published

1981
1981
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(74 citation statements)
references
References 71 publications
3
64
1
6
Order By: Relevance
“…For this reason, self-control is lower in the group of patients with anxiety disorders than in the other groups. Patients anxiety is also associated with the fear of death, still, those with a positive sense of well-being present less fear (Pollak, 1980). The present study also confirms that the general health of breast cancer patients is worse in patients diagnosed with depressive disorder.…”
Section: Discussionsupporting
confidence: 84%
“…For this reason, self-control is lower in the group of patients with anxiety disorders than in the other groups. Patients anxiety is also associated with the fear of death, still, those with a positive sense of well-being present less fear (Pollak, 1980). The present study also confirms that the general health of breast cancer patients is worse in patients diagnosed with depressive disorder.…”
Section: Discussionsupporting
confidence: 84%
“…Women in our study reported more anxiety/fear about death. In a survey of research studies on death fear by sex, Pollack (1979) reported that the majority of findings concluded that women reveal more death fear than men. Judith Stillion (1985), however, suggested that there is a greater tendency for women to admit troubling feelings than men.…”
Section: Discussionmentioning
confidence: 99%
“…Age was an inconsistent determinant in the literature, so in some studies investigators found that death anxiety was not higher in older people compared to the younger (16,17), but other studies found that age monotonically increases with death anxiety level (29).…”
Section: Discussionmentioning
confidence: 99%